THE EFFECT OF ADVERTISING, TRUST, AND RISK PERCEPTION ON PRODUCT PURCHASE DECISIONS - Siti Fatimah; Hendri Hermawan Adinugraha (IAIN Lhokseumawe, 2023)
Many businesses and sellers turn to e-commerce platforms to offer their products. The development of this technology online sellers must make creative and innovative marketing strategies to attract consumer interest. Purchase decisions on online buying and selling sites are strongly influenced by advertising, consumer trust in sellers, and perceived risks to minimize dissatisfaction with a product. The purpose of this study was to analyze the influence, namely the influence of advertising, trust, and risk perception on the purchasing decisions of Shopee e-commerce products. The population in this study is iGen or Generation Z as many as 35 respondents. This research method is quantitative by using non-probability sampling technique. Hypothesis testing using multiple linear regression analysis. Based on data analysis, it was found that 91% of advertising, trust, and risk perception variables had a significant effect on purchasing decisions for Shopee e-commerce products among iGen.